Spatial model of industrial area suitability using spatial multi criteria evaluation: A case study in Kendari City - Septianto Aldiansyah Septian; Randi Adrian Saputra (Sustinere: Journal of Environment and Sustainability, 2022)
Designing an industrial location must be based on consideration of factors that will influence it such as natural, environmental and ecological conditions. One of the spatial-based location determination methods is Spatial Multi-Criteria Evaluation (SMCE). This study aims to determine suitable industrial areas and compare industrial locations that have been determined based on the Regional Spatial Plan (RTRW) for 2010-2030 in Kendari City. Industrial areas must be flood-free, located in a relatively flat area, far from settlements, have good access and must not interfere with the river’s natural function. Therefore, the aspects of access, hydrology, physiography and convenience were all taken into account in this study. The area in Scenario A was retested with Scenario B and Scenario C to get a variety of industrial areas with different perspectives. Kendari City’s appropriate industrial area is 2.462.36 ha and is located in Puuwatu Sub-District, which is directly connected to Mandonga Sub-District (scenario 2.C). The RTRW map with the industrial model of the area shows the mismatch of the proposed industrial area placement. The results of this industrial area can be used as an alternative for decision-makers.